Artikulasi Fungsi Ruang Terbuka sebagai Pembentuk Landmark Perkotaan - Imriyanti Imriyanti; Nurmaida Amri (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Makassar as the largest city in the eastern Indonesia has the growth and development of the various sectors. The growth and the development are at the core of development in urban areas. Development is also leading to the award character to the city of Makassar. Losari Beach Pier is the place openly in the area of coastal communities and enabled by Makassar city as a place of relaxation and recreation. With this function, the problem of this research is how the articulation function of the open space at the Pavilion Losari Beach Makassar Makassar Losari whether the Pavilion can be a landmark of Makassar as a whole, what is the frequency of the use of the Pavilion Losari community interaction system as the wearer. This study aims to examine the functional articulation of open space in the Pavilion Losari Beach as Makassar’s landmark. The method used in this study was a qualitative descriptive study that produced data in the systematic form and accurate description of the object of study. This study also used the case study design and test against a context of a particular subject, a collection of documents and a special study, while the frequency are assessed by statistic method. Functional articulation of open space at the Pavilion Losari includes location, appereance, and function. Location refers to Losari Beach Pier’s location on coastal areas. It had been used as connecting line, called Maminasata, from several counties to the city of Makassar. Appereance refers to the existence of Losari Beach as the new icon and the landmark of Makassar. It became a symbol of the culture of Makassar. Function refers to the ability of Losari Beach as open space to gather the entire community who want to do the recreation and leisure activities in the city center. In this place, the direct interaction occures significantly such as visiting and trading. This interaction occurred because there are differences between the visitors and traders’ areas.